Pengembangan Formula Spray Gel Ekstrak Etanol Daun Komba- Komba (Eupatorim Odoratum) Sebagai Kandidat Repellent - Michrun Nisa; Irmayani Irmayani; Sweety Dwy Sarty (Jurnal Farmasi & Sains Indonesia, 2022)
Repellent is an insecticide that is used to protect the skin from mosquito bites. Spray gel is a form of developing gel preparations applied through a pump spray. Ethanol extract of komba – komba (Eupatorium odoratum) leaves with a concentration of 7% has mosquito repellent activity because it contains compounds that are toxic to mosquitoes. 100% protection at the 1st hour followed by 73% at the 6th hour. This study aims to formulate the ethanolic extract of komba-komba leaves in the form of a spray gel with a variation of the gelling agent carbopol 940: HPMC, namely, 0.5%: 0.25%; 1% : 0.5% ; and 1.5% : 0.75%. Physical evaluation of the preparation includes organoleptic test, pH test, viscosity test, spray pattern test and dry time. The evaluation results show that formula 2 meets the param eters of the physical properties of the spray gel preparation